Implementasi Pembelajaran Fiqih Materi Sholat Dengan Media Audio Visual Di Madrasah Ibtidaiyah - Sodikin, Sodikin; Ashom, Khotim (EDUCARE: Journal of Primary Education, 2021)
This research was conducted to form students to be more disciplined in maintaining time, especially in prayer, as well as to strengthen aqidah and increase the worship of students of Madrasah Ibtidaiyah Salafiyah Syafi'iyah. The focus of this research is: 1) How to plan the prayer chapter of fiqh learning through audio-visual media for students of Class IV Madrasah Ibtidaiyah Salafiyah Syafi'iyah Ajung, 2) How to implement the prayer chapter of fiqh learning through audio-visual methods for students of Class IV Madrasa Ibtidaiyah Salafiyah Syafi 'iyah Ajung, 3) How is the evaluation of fiqh learning in the prayer chapter for fourth grade students of Madrasah Ibtidaiyah Salafiyah Syafi'iyah Ajung. This research uses qualitative research with descriptive qualitative research. Determination of research subjects in this study was carried out purposively. Data collection techniques used observation, interviews, and documentation. Analysis of the data, the researcher used the data analysis model of the Miles, Huberman, and Saldana models including: Data Condensation (Condensation), Data Presentation (Display), Conclusions Drawing. The validity of the data in this study used source triangulation and technical triangulation. The results showed that: 1) The use of audiovisual media was very relevant in learning fiqh in the prayer chapter 2) Active, innovative, creative, effective and fun learning made students enthusiastic and enthusiastic in learning and not boring. 3) the completeness of learning facilities and infrastructure is very influential in the evaluation stage including summative evaluation and formative evaluation, input evaluation, process evaluation and output evaluation. Keywords: Implementation; Fiqh learning; Audio visual Penelitian ini dilakukan untuk membentuk peserta didik lebih disiplin dalam menjaga waktu khususnya dalam shalat, serta memantapkan aqidah dan meningkatkan ibadah peserta didik Madrasah Ibtidaiyah Salafiyah Syafi’iyah. Fokus penelitianini adalah: 1) Bagaimana Perencanaan Pembelajaran fiqih bab sholat melalui media audio visual bagi peserta didik Kelas IV Madrasah Ibtidaiyah Salafiyah Syafi’iyah Ajung, 2) Bagaimana Pelaksanaan pembelajaran fiqih bab sholat melalui metode audio visual bagi peserta didik Kelas IV Madrasah Ibtidaiyah Salafiyah Syafi’iyah Ajung, 3) Bagaimana evaluasi pembelajaran fiqih bab sholat bagi peserta didik kelas IV Madrasah Ibtidaiyah Salafiyah Syafi’iyah Ajung. Penelitian ini menggunakan penelitian kualitatif dengan jenis penelitian kualitatif deskriptif. Penentuan subyek penelitian dalam penelitian ini dilakukan secara purposive.Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data, peneliti menggunakan model analisis data model Miles, Huberman, dan Saldana meliputi: Kondensasi Data (Condensation), Penyajian Data (Display), Penarikan Kesimpulan (Conclusions Drawing). Keabsahan data dalam penelitian ini menggunakan triangulasi sumber dan triangulasi teknik.Hasil penelitian menunjukkan, bahwa: 1) Penggunaan media audiovisual sangat relevan dalam pembelajaran fiqih bab sholat 2) Pembelajaran aktif, inovatif, kreatif, efektif, dan menyenangkan membuat peserta didik semangat dan antusias dalam belajar serta tidak membosankan. 3) kelengkapan sarana dan prasarana pembelajaran sangat berpengaruh pada tahap evaluasi meliputi evaluasi Sumatif dan evaluasi Formatif evaluasi input, evaluasi proses dan evaluasi output.  Kata Kunci: Implementasi; Pembelajaran Fiqih; Audio Visual